2017
DOI: 10.1177/1049732317723316
|View full text |Cite
|
Sign up to set email alerts
|

Struggles Over Antibiotics: Physicians’ Stance-Taking Toward a Nonconforming Policy in an Intensive Care Unit

Abstract: One of the most pressing contemporary health care challenges consists in rethinking antibiotic use to contrast the increase of multidrug resistant bacteria. Drawing on an ethnographic fieldwork in an Intensive Care Unit that adopts a nonconforming policy of antibiotic stewardship, this article analyzes doctor-doctor interaction concerning infectious disease diagnosis and antibiotic treatment. By analyzing examples of medical decision-making from a corpus of video-recorded morning briefings, we focus on physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…There is still a limited body of EM/CA studies that examine team meeting interaction among medical professionals (e.g. Beck Nielsen, 2014; Caronia et al, 2017; Caronia and Saglietti, 2017, 2018; Ikeya and Okada, 2007; Izumi, 2014, 2017a, 2017b; Turowetz, 2015). One of the key areas these studies deal with is distribution of knowledge among various specialists.…”
Section: Professional Clinical Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still a limited body of EM/CA studies that examine team meeting interaction among medical professionals (e.g. Beck Nielsen, 2014; Caronia et al, 2017; Caronia and Saglietti, 2017, 2018; Ikeya and Okada, 2007; Izumi, 2014, 2017a, 2017b; Turowetz, 2015). One of the key areas these studies deal with is distribution of knowledge among various specialists.…”
Section: Professional Clinical Practicesmentioning
confidence: 99%
“…Moreover, the article adds to the body of knowledge in a relatively underexplored area in medical conversation analysis (CA), especially diagnostic and decision-making practices among medical professionals (e.g. Beck Nielsen, 2014; Caronia et al, 2017; Caronia and Saglietti, 2017, 2018; Ikeya and Okada, 2007; Izumi, 2017a, 2017b; Turowetz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research on antibiotic prescribing in general has found that doctors typically focus on the immediate risk of infection for their individual patients rather than the communal, future risk of AMR (Broom et al, 2014;Krockow et al, 2019). It has also been observed that antibiotics are prescribed to appease other staff, patients, and families in hospitals (Lewis and Tully, 2009;Charani et al, 2013), that there are problems in interaction between different staff, patients and clinical domains (Skodvin et al, 2017;Saukko et al, 2019), junior doctors are confused by contradictory advice (Mattick et al, 2014;Kajamaa et al, 2019) and that professional identities (Broom et al, 2016) and "off label" local cultures fuel prescribing (Caronia and Saglietti, 2017).…”
Section: Introductionmentioning
confidence: 99%